Charge Compensation in Trivalent Doped Ca3(SiO4)Cl2. Issue 1744 (2015) - Gilbert, M. R.
ABSTRACT: Calcium chlorosilicate (Ca3 (SiO4 )Cl2 ) is seen as a potential host phase for the immobilization of Cl-rich wastes arising from pyrochemical reprocessing, a waste stream often containing a mix of both di- and trivalent cations. Substitution of trivalent cations into the lattice requires some form of charge compensation to ensure the lattice remains charge neutral overall. Whilst previous work has only examined this through the formation of Ca vacancies, this study investigates the feasibility of charge-balancing via the substitution of a monovalent cation onto the Ca sites of the lattice. To that end, a series of static lattice calculations were performed to determine the site selectivity of monovalent cations of differing size when substituted onto the Ca sites of the calcium chlorosilicate lattice and the solution energies for the overall substitution processes compared with those for charge compensation via vacancy formation. In all cases the monovalent charge-balancing species shows a clear preference for substitution onto the Ca1 site in the calcium chlorosilicate lattice. The solution energy of the substitution process increases with the increasing ionic radii of both the mono- and trivalent species as the steric stresses associated with substitution of larger cations than the Ca 2+ host increase. As such, only charge-balancing using Li +, Na + or K + is more favourable than via formation of a Ca vacancy.